Sleep quality and its associated factors among patients with tuberculosis: A cross-sectional study - Liu, Xiangmin; Lan, Huizhen; Bai, Xinyu; Li, Qian; Wen, Yan; Feng, Mei; Tang, Xiangdong (Frontiers in Public Health, 2023)
Abstract Background: Tuberculosis (TB) patients commonly suffer from sleep issues owing to various adverse drug reactions (ADRs), disease symptoms, and the contagious nature of their disease. These sleep issues negatively affect the treatment outcome and quality of life. However, the prevalence of sleep disturbance and its associated factors among TB patients have rarely been reported. Methods: A total of 497 inpatients with TB from three hospitals in China were enrolled in this cross-sectional study to investigate their sleep quality using the Pittsburgh sleep quality index (PSQI). Clinical data, including demographic information, TB-related stigma, perceived stress, and nutrition- and immunity-related indicators, were also collected to explore the factors associated with sleep disturbance among the recruited patients. Results: Approximately 70% of the recruited patients reported a sleep disturbance to varying degrees, presenting poorer global and subjective sleep qualities, longer sleep latency, shorter sleep duration, lower sleep efficiency, more frequent sleep disturbances, greater use of sleeping medication, and more severe daytime dysfunction. Furthermore, the body mass index (BMI), hemoglobin levels, albumin levels, and T lymphocyte count of the patients in the poor sleep quality group were significantly lower than those in the good sleep quality group (p < 0.05). Increasing age, higher income, drug resistance, higher stigma or stress perception, lower albumin levels, and lower CD4 levels were significantly associated with sleep disturbance among TB patients (p < 0.05). Conclusion: Three-quarters of the participants were found to suffer from a probable sleep disturbance. It is therefore important to pay attention to the sleep quality of TB patients, especially those with the identified risk factors.